2011
DOI: 10.1007/s10096-011-1351-6
|View full text |Cite
|
Sign up to set email alerts
|

Prospective audit and feedback on antibiotic prescription in an adult hematology-oncology unit in Singapore

Abstract: We evaluated the impact of a prospective audit and feedback antimicrobial stewardship program (ASP) on antibiotic prescription and resistance trends in a hematology-oncology unit in a university hospital (National University Cancer Institute, Singapore [NCIS]). A prospective interrupted time-series study comprising 11-month pre-intervention (PIP) and intervention evaluation phases (IEP) flanking a one-month implementation phase was carried out. Outcome measures included defined daily dose per 100 (DDD/100) inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 17 publications
4
66
0
4
Order By: Relevance
“…The review of the reference lists of the full-texted articles yielded two additional studies. As a result, 26 studies coded from 25 articles (1 article presented data from two different hospitals [28]) were included in our meta-analysis. The information extracted from individual studies is exhibited in Table 1, and the detailed selection process is illustrated in a flow chart (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The review of the reference lists of the full-texted articles yielded two additional studies. As a result, 26 studies coded from 25 articles (1 article presented data from two different hospitals [28]) were included in our meta-analysis. The information extracted from individual studies is exhibited in Table 1, and the detailed selection process is illustrated in a flow chart (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ID physicians provide a standard referral service whereas the prospective audit and feedback system of our ASP is also standard and has been described elsewhere [4,5]. Clinical and demographic data were extracted from our ASP database as well as the hospital electronic records.…”
Section: Setting and Methodsmentioning
confidence: 99%
“…In our institution, where a prospective audit and feedback ASP has been established since 2009 [4], we have consistently taken the last approach. We present herein our experience where ASP and ID physicians provide independent assessments and recommendations, analyzing the outcomes of a large subset of cases where the recommendations have differed.…”
Section: Introductionmentioning
confidence: 99%
“…Many countries have few antibiotic prescription control policies in the hospital setting and either have no antibiotic stewardship programs in place or are just beginning to implement such programs; a recent international survey showed that just over half (53%) of Asian countries had any form of antibiotic stewardship in their hospitals, and of those that did, fewer than half had any national (42%) or regional (16%) antibiotic stewardship standards in place (170). In countries with fairly established antibiotic stewardship programs such as Singapore, adherence to antibiotic prescription recommendations seldom exceeded 75% in published reports (171,172). In India, it was reported that physicians were compensated by pharmaceutical companies and phar-macies for prescribing antibiotics (166), but it is unclear how prevalent this practice is in other countries.…”
Section: Drivers Of Carbapenem-resistant Gram-negative Bacteriamentioning
confidence: 99%